2014
DOI: 10.1177/2047487314550803
|View full text |Cite
|
Sign up to set email alerts
|

Polypill for the prevention of cardiovascular disease (PolyIran): study design and rationale for a pragmatic cluster randomized controlled trial

Abstract: Background The complexity of treatment regimens, costs and pill burden decrease the medication adherence and contribute to shortfall in cardiovascular preventive drug coverage. The polypill, a fixed dose combination pill of established drugs is expected to increase adherence and reduce the costs whilst preventing the major cardiovascular events (MCVE). Design and methods The PolyIran trial is a pragmatic cluster randomized trial nested within Golestan Cohort Study (GCS). Subjects were randomized to either no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Interventions to improve patient adherence and persistence on secondary preventive medicines has been at the forefront of recent discussions by the World Health Organization [19] for which various interventions including tele-medicine approaches are being evaluated some of which have shown preliminarily promising results with others on-going and due to report [20] , [21] , [22] , [23] . Implementation and widespread penetration of these interventions into routine care particularly in LMICs is anticipated as well as strategies to simplify treatment for stroke survivors such as the use of the Cardiovascular Polypill which contain antihypertensive agents, lipid modifiers and anti-thrombotic agents which are also undergoing experimental trials to evaluate their efficacy in both primary and secondary prevention [24] , [25] , [26] , [27] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to improve patient adherence and persistence on secondary preventive medicines has been at the forefront of recent discussions by the World Health Organization [19] for which various interventions including tele-medicine approaches are being evaluated some of which have shown preliminarily promising results with others on-going and due to report [20] , [21] , [22] , [23] . Implementation and widespread penetration of these interventions into routine care particularly in LMICs is anticipated as well as strategies to simplify treatment for stroke survivors such as the use of the Cardiovascular Polypill which contain antihypertensive agents, lipid modifiers and anti-thrombotic agents which are also undergoing experimental trials to evaluate their efficacy in both primary and secondary prevention [24] , [25] , [26] , [27] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical trials with polypill have been focused mainly on its effects on medication adherence and cardiovascular risk factors control. Fortunately, different clinical trials are now determining whether the beneficial effect of polypill on medication adherence translates into a lesser risk of cardiovascular outcomes [47,60,[72][73][74][75]. For example, the SECURE European study, coordinated by the CNIC, is now assessing whether a fixed dose combination polypill for secondary cardiovascular prevention in the elderly population (≥65 years old) may reduce cardiovascular events (death from cardiovascular causes, nonfatal myocardial infarction, stroke and hospitalization requiring revascularization) as compared with standard therapy (the three components of the polypill given separately).…”
Section: Future Perspectivementioning
confidence: 99%
“…11,13,31 Results of various under way trials (SECURE, PolyIran, TIPS-3, and HOPE-4, among others) are expected to provide the evidence about the effects and safety of polypills. [32][33][34] It is also worth highlighting that many trials that have evaluated prevention is yet to be demonstrated. 11,13,21 The concept of polypills in the primary prevention of CVD was first introduced by Wald and Law, 14 who presented these drugs as a mass treatment strategy to reduce CVD by more than 80%.…”
Section: Available 11mentioning
confidence: 99%